Plan estratégico de marketing relacional en las empresas comercializadoras de carne faenada, Canton Buena Fe, periodo 2015 – 2018 - Flores Aguirre, Cristian Fabián (2015)
The population growth and the migration of the field to the cities, as well as, the population's preferences, they have generated the growing necessity of this product, for that that this market, you restitution almost irreplaceable. However, a limited presence of big companies dedicated to this activity exists, what has been favorable for the opening of small and medium companies at local, regional and national level. The canton Buena Fe possesses a total of 63.148 inhabitants (ONEC, 2010), this located in one of the regions of bigger importance of the agricultural and commercial sector of the county of The rivers, for what an important market that should be assisted with products of quality and good price exists. However, the local of it expended of meat butchered they don't offer an appropriate service neither they carry out activities of diffusion of their local and product, motivating that most of the population prefers to acquire it in the supermarkets of the city of Quevedo, limiting with it the managerial development. For that pointed out, the present work is justified since it is of vital importance to carry out a study in that it is analyzed the strategies that should be executed in the Plan of Marketing to contribute substantially in the improvement of the service, productivity and its proprietors' profitability. For that pointed out, the present work is justified since it is of vital importance to carry out a study in that it is analyzed the strategies that should be executed in the Plan of Marketing to contribute substantially in the improvement of the service, productivity and its proprietors' profitability.